Energetic Neutral Atoms From Jupiter's Polar Regions. Issue 12 (21st December 2020) - Mauk, B. H.; Allegrini, F.; Bagenal, F.; Bolton, S. J.; Clark, G.; Connerney, J. E. P.; Gladstone, G. R.; Haggerty, D. K.; Kollmann, P.; Mitchell, D. G.; Paranicas, C. P.; Roelof, E. C.; et al.
Abstract: Energetic Neutral Atom (ENA) cameras on orbiting spacecraft at Earth and Saturn helped greatly to diagnose these complex magnetospheres. Within this decade, the European Space Agency's Jupiter Icy Moons Explorer will make ENA imaging a major thrust in understanding Jupiter's complex magnetosphere. The present polar‐orbiting Juno mission at Jupiter carries no ENA camera. But, the Jupiter Energetic‐particle Detector Instrument is sensitive to >50 keV ENAs, provided there are no local charged particles to mask their presence. Juno offers great service to interpreting past serendipitous and future dedicated ENA imaging with its orbit providing unique viewing perspectives. Here we report Juno observations of ENAs from Jupiter's polar regions. These ENAs likely arise from energetic ions that nearly precipitate in the main auroral regions and mirror magnetically within, and charge exchange with, Jupiter's upper atmosphere. Jupiter proves itself different from Saturn, as ENAs generated from precipitating ions were not identified there. Plain Language Summary: In the space environments (called magnetospheres) of magnetized planets, singly charged energetic particles, trapped by the planet's magnetic field, can steal electrons from cold gas atoms and become neutralized. These now Energetic Neutral Atoms (ENAs), no longer confined by the magnetic field, can travel out of the system similar to photons leaving a hot oven. ENA cameras on orbiting spacecraft at Earth and Saturn have helped greatly to diagnose these complex magnetospheres. The present polar‐orbiting Juno mission at Jupiter carries no ENA camera. But, the Jupiter Energetic‐particle Detector Instrument is sensitive to ENAs with energies >50 keV, provided there are no charged particles in the environment to mask their presence. Here we report on Juno observations of ENAs coming from Jupiter's polar regions. These ENAs likely arise from energetic ions that nearly precipitate, reaching the atmospheric regions of Jupiter's main aurora and mirroring magnetically within Jupiter's upper atmosphere. Key Points: Energetic Neutral Atoms (ENAs) with energies >50 keV are observed to be emitted from Jupiter's north polar regions These ENAs appear to be from precipitating energetic ions that magnetically mirror within the upper atmosphere of Jupiter's main aurora Findings support previous proposals that precipitating ions contribute greatly to Jupiter ENA emissions, contrary to findings at Saturn